Histological study of the quail spleen (Coturnix coturnix coturnix ): Luay O.Hamza , Khawla J.Balash - Hamza, Luay O. (The Iraqi Journal of Veterinary Medicine, 2005)
The present study revealed that the spleen of the quail is coated byafibrous capsule have two distinct layers , an outer and inner , the capsule beingcovered by athin layer of peritoneal membrane . The spleen comprises twodistinct regions , the white pulp and red pulp in addition spares or trabecule .The white pulp represernt the major part of the organ , it is alymphatic tissuethat could be differentiate into two forms : diffuse and nodular lymphatic tissuewith medium and small size arteries represent the branches extend from thelarge trabecular arteries . Then these arteries branch into arterioles surroundedby sheath of reticular and lymphatic cells called Schweigger Sediel sheath .The red pulp has randomly distributed between the white pulp regions , itconsist of cellular cord that surround the venous sinuses which had irregularshape lined endothelial cells separated by small gaps freely .The capsule consist of two layer , an outer layer that represent largecollagen fiber while the inner layer represent large muscular fiber , thus themarginal zone between the white and red pulp is absent . the ellipsoid body waspresent in the white pulp more than the red pulp . In this study there are two typeof nodules , type T nodule and type B were present . The percentage of the firstnodular type is more than the second , which is the important character of thespleen of quail differ from other fowl